The Legality of Public Pension Reforms in Times of Financial Crisis : The Case of Greece - Diliagka, Dafni (Nomos Verlagsgesellschaft mbH & Co. KG, 2018)
The first reactions to the Greek financial crisis were pension reforms and reductions. The aim of this book is to assess the legal implications of the reductions to pension benefits, proposing a legal framework in which pensioners are able to raise legal claims in court. The book gives account of the background regarding the factors that necessitated pension reforms prior to and after the fiscal crisis. Furthermore, it describes the Greek pension reforms and reductions which were undertaken progressively by the Greek Parliament from the beginning of the crisis until the year 2012. Finally, it examines the legality of the public pension reforms and reductions in old-age pension benefits with the Greek Constitution and with international law. The assessment is achieved using the principle of proportionality as a balancing concept.
English
Keywords: Greece; Public Pension Reforms; Sozialrecht; Griechenland; Finanzkrise; Rentenkürzungen; finanzieller Notstand; Rente